City, Self, and Spectacle: Urban Psyche in Desai and Hussain - Adhikari, Tej Narayan (NPRC Journal of Multidisciplinary Research, 2025)
Background: City Studies has emerged as a highly interdisciplinary academic field, addressing critical issues such as urban development, social inequality, globalization, and the impact of technology on urban life. This study examines the urban psyche depicted in Anita Desai’s “The Farewell Party” (1980) and Intizar Hussain’s “Noise” (2014). Methods: Both stories are set in unspecified South Asian urban environments and explore the complex relationship between individuals and the modern city. The analysis focuses on the psychological effects of social dynamics, urban isolation, fleeting connections, and urban anxieties, as articulated through Simmel’s concepts. Result: Desai’s story illustrates how a farewell party becomes a stage for superficial social interactions, revealing hidden emotions and tensions among city dwellers. This aligns with Simmel’s notion of the ‘blasé attitude,’ which serves to maintain social equilibrium. Hussain’s story portrays the city as a source of noise and chaos, reflecting Simmel’s idea of the metropolis as a cause of psychological stress. Conclusion: Both narratives exemplify Simmel’s concept of the urban psyche, where individuals grapple with loneliness, performative relationships, and the sensory overload of modern urban environments. Novelty: This study highlights how Desai and Hussain’s works provide literary insights into the psychological challenges posed by metropolitan life, reinforcing Simmel’s theories on urban mental life.